Doenças sexualmente transmissíveis na infância - Figueiredo, Paula Alexandra Leite; Passos, Mauro Romero Leal; Pinheiro, Vandira Maria dos Santos; Barreto, Nero Araújo; Vianna, Altamiro; Carvalho, Vilhena de; Bravo, Renato de Souza (Brazilian Journal of Sexually Transmitted Diseases, 1997)
Sexually Transmitted Diseases (STDs) in children may be trasnsmitted by sexual abuse, by accidental contact, or perinatally. To determine frequency, prevalence, routes of the transmission, and clinicai features of these infections in our patients we examine the records of ali 22 patients between 0 and 10 years old, seen at Setor de DST/ UFF - Niteroi- RJ, over a seven year period (1988-1996). The age range was five years and three months and 68% were girls. The majority (36%) of the ch ildren presented with genital discharge as the chief complaint, followed by genital and anal warts in 27,3%. Sexually Transmitted Diseases was identified in sixteen (77%) of the 22 child-ren: six cases of inespecific vulvovaginitis, four cases of HPV, two cases of syphilis and one case of gonorrhea and Candidiase. We didn't find any children with HN/ AIDS. Sexual contact, was the probably rout of transmission in children with syphilis and Gonorrhea. Accidental contact with their infected parents occurred in patients with HPV and Candidiase. Since we found alleged sexual abuse in our study. we thing that. all children with genital and annal complaint, must be investigate one STDs and when they occur, sexual abuse must be rulled out.